Students’ Perceptions on Business English Writing through Business Plan in English for Business - Ratnaningsih, Paskalina Widiastuti (English Education and Literature Journal (E-Jou), 2026)
The aim of this study is to discover business English writing through business plan. English for Specific Purposes focuses on English learning that is specified for purposes in each different field. By mastering specified materials based on the purpose of learning, then students have specified competence in their field. English for Business is one of English for Specific Purpose fields. Writing is one of English skills that is challenging to be learned. In the Entrepreneurship study program, business plan is needed so that the students are able to build a business after graduation. The ability to write business plan in English is needed. This study used survey research. The respondents of this study were English for Business class students in Entrepreneurship study program that consisted of 23 students. The study used questionnaire that was divided into closed-ended and open-ended questions. The results of this study were students’ ability in business English writing increased in the number of 52%. The students could write sentences and paragraphs well and their vocabulary in business English increased. They could write business plan in English well. It also increased collaboration among students. Future researchers can explore other skills for research of business English in Entrepreneurship study program.